The progression of flood risk in southern Alberta since the 2013 flood. Issue 3 (21st June 2022) - Bryant, Seth P.; Davies, Evan G. R.; Sol, David; Davis, Sandy
Abstract: After a century of semi‐restricted floodplain development, Southern Alberta, Canada, was struck by the devastating 2013 Flood. Aging infrastructure and limited property‐level floodproofing likely contributed to the $4–6 billion (CAD) losses. Following this catastrophe, Alberta has seen a revival in flood management, largely focused on structural protections. However, concurrent with the recent structural work was a 100, 000+ increase in Calgary's population in the 5 years following the flood, leading to further densification of high‐hazard areas. This study implements the novel Stochastic Object‐based Flood damage Dynamic Assessment (SOFDA) model framework to quantify the progression of the direct‐damage flood risk in a mature urban neighborhood after the 2013 Flood. Five years of remote‐sensing data, property assessment records, and inundation simulations following the flood are used to construct the model. Results show that in these 5 years, vulnerability trends (like densification) have increased flood risk by 4%; however, recent structural mitigation projects have reduced overall flood risk by 47% for this case study. These results demonstrate that the flood management revival in Southern Alberta has largely been successful at reducing flood risk; however, the gains are under threat from continued development and densification absent additional floodproofing regulations.